Seasonal variation in microbial profile of Automated Teller Machines (ATMs) in and around University of Port Harcourt, Choba, Nigeria - Amarachi Odoemelam, Helen; Ogugbue-Jason, Chimezie; Aniebo-Mbakwem, Chiaka (Macedonian Journal of Ecology and Environment, 2020)
The Automated Teller Machine (ATMs) has been widely and publicly used for transactions by bank customers. The individuals that use this machine come from different homes and background, and there is every likelihood that some of them are carriers of diverse microorganisms. The objective of the present study was to investigate the seasonal variation in the microbial profile of the contact surface of ATMs in and around University of Port Harcourt, Choba, Nigeria. The samples were collected during the dry and rainy seasons. The sampling was done three times in a day; Morning 8–9 am, afternoon 1–2 pm, evening 5–6 pm, from different ATMs using moistened sterile swab sticks. The study recorded that during rainy and dry seasons, the total heterotrophic bacterial count ranged from log10 4.08 to 9.56 CFU/m2 and log10 3.08 to 7.80 CFU/m2 respectively. The total fungal counts in rainy and dry seasons were log10 3.38 to 7.52 CFU/m2, log10 3.08 to 6.48 CFU/m2 respectively. The frequency of occurrence of fungi during rainy and dry seasons were 30% and 28% respectively. The 16s RNA sequence analysis was carried out on the bacterial and fungal isolates. The different samples (A, B, C, D, E, F, G, H, I, J) showed significant differences (p<0.05) in the number of microorganisms between different collection periods, except for total fungal count for sample C during the dry season and sample D during the rainy season. Further findings showed that Bacillus cereus had the highest occurrence of 10 (15.9%) and 9(17%) respectively in the rainy and dry seasons, while Proteus mirabilis and Comamonas aquatica had the lowest occurrence 2(2.63%), 2(2.63%) respectively in the rainy season. Escherichia coli and Comamonas aquatica were not isolated during the dry season. Aspergillus niger had the highest frequency of occurrence 8(27%) in both seasons, Kodamaea ohmeri had the lowest occurrence in both seasons. This study highlights the need for banks to take preventive measures against spread of infectious diseases through ATMs by regularly cleaning the ATMs surfaces with disinfectant and for users of ATM to always wash their hands after using the machine.